Projecting Future Fire Regimes in a Semiarid Watershed of the Inland Northwestern United States: Interactions Among Climate Change, Vegetation Productivity, and Fuel Dynamics. Issue 3 (1st March 2022) - Ren, Jianning; Hanan, Erin J.; Abatzoglou, John T.; Kolden, Crystal A.; Tague, Christina (Naomi) L.; Kennedy, Maureen C.; Liu, Mingliang; Adam, Jennifer C.
Abstract: Fire regimes are influenced by both exogenous drivers (e.g., increases in atmospheric CO2 and climate change) and endogenous drivers (e.g., vegetation and soil/litter moisture), which constrain fuel loads and fuel aridity. Herein, we identified how exogenous and endogenous drivers can interact to affect fuels and fire regimes in a semiarid watershed in the inland northwestern United States throughout the 21st century. We used a coupled ecohydrologic and fire regime model to examine how climate change and CO2 scenarios influence fire regimes. In this semiarid watershed, we found an increase in burned area and burn probability in the mid‐21st century (2040s) as the CO2 fertilization effect on vegetation productivity outstripped the effects of climate change‐induced fuel decreases, resulting in greater fuel loading. However, by the late‐21st century (2070s), climatic warming dominated over CO2 fertilization, thus reducing fuel loading and burned area. Fire regimes were shown to shift from flammability‐ to fuel‐limited or become increasingly fuel‐limited in response to climate change. We identified a metric to identify when fire regimes shift from flammability‐ to fuel‐limited: the ratio of the change in fuel loading to the change in its aridity. The threshold value for which this metric indicates a flammability versus fuel‐limited regime differed between grasses and woody species but remained stationary over time. Our results suggest that identifying these thresholds in other systems requires narrowing uncertainty in exogenous drivers, such as future precipitation patterns and CO2 effects on vegetation. Plain Language Summary: While many studies have projected increases in wildfire under future climate change, fire may eventually decrease in some locations. The direction and extent of fire regime changes depend in large part on how decreases in fuel moisture balance against increases or decreases in fuel loading, which can occur in response to warmer temperatures and increasing atmospheric CO2 concentrations. The balance between fuel moisture and loading, and their relative importance in driving fire regimes can vary along moisture gradients in western North America. To project how wildfire size, frequency, and severity will change in a relatively arid watershed of the northwestern United States throughout the 21st century, we used a coupled vegetation, water, and fire spread model. We found that wildfire is likely to increase in the mid‐21st century due to an increase in fuel production and drier fuel. However, wildfire will likely to decrease in the late‐21st century due to warming‐induced increases in fuel decomposition, even when fuels are drier. We demonstrate that future wildfire regimes are dynamic, so the linear extrapolation of fire size from the baseline and 2040s scenarios to the 2070s may not always be a suitable approach, and we need to consider complex fuel responses to climate change. Predicting future wildfires will require reducing key uncertainties in future precipitation patterns and understanding how CO2 fertilization affects plant growth. Key Points: Burned area in a semiarid watershed in Idaho is projected to increase in the 2040s and decrease in the 2070s While climate change decreases burned area by reducing fuel load, CO2 fertilization counteracts this effect to some extent For a given vegetation type, there are temporally stable thresholds that determine whether a location is fuel or flammability limited